PENGGUNAAN MEDIA KARTU UNTUK MENINGKATKAN HASIL BELAJAR MEMBACA TEKS NARRATIVE PADA SISWA KELAS IX B SMP NEGERI 3 TRENGGALEK - DENI SUSANTO (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
The aim of writing this Best Practice is to determine the use of card media to improve learning outcomes for reading narrative texts in class IX B students of SMP Negeri 3 Trenggalek Semester II 2019/2020 academic year. Want to know the extent of the impact of using card media to improve learning outcomes for reading narrative texts in Class IX B students of SMP Negeri 3 Trenggalek Semester II 2019/2020 academic year. Theoretically, the results of this best practice can contribute positive thinking in science in the field of education, especially in the application of learning media using cards in English subjects in junior high schools. The learning process using learning media in the form of cards makes students more active in learning and students try to foster an attitude of working together. Students become more interested in learning without being burdened and not easily bored in learning activities. Learning outcomes for reading narrative texts for class IX students in the even semester of the 2019/2020 academic year at SMPN 3 Trenggalek have increased with an average student score of 84.53 with a completion percentage of 100%. Based on the results, the average student score was 84.53 with the number of students who completed the indicators being 32 students (100% of the total number of students). ABSTRAKTujuan dari penulisan Best Practice ini adalah mengetahui penggunaan media kartu untuk meningkatkan hasil belajar membaca teks narrative pada siswa kelas IX B SMP Negeri 3 Trenggalek Semester II Tahun Pelajaran 2019/2020. Ingin mengetahui sejauh mana dampak dari penggunaan media kartu untuk meningkatkan hasil belajar membaca teks narrative pada siswa Kelas IX B SMP Negeri 3 Trenggalek Semester II Tahun Pelajaran 2019/2020. Secara teoretis, hasil best practice ini dapat memberikan sumbangan pemikiran yang positif dalam ilmu pengetahuan di bidang pendidikan, khususnya dalam penerapan media pembelajaran dengan menggunakan media kartu pada mata pelajaran Bahasa Inggris di Sekolah Menengah Pertama. Proses pembelajaran dengan media pembelajaran berupa kartu membuat siswa menjadi lebih aktif dalam pembelajaran dan siswa berusaha menumbuhkan sikap saling bekerja sama. Siswa menjadi lebih tertarik untuk belajar tidak terbebani dan tidak mudah jenuh dalam kegiatan pembelajaran. Hasil belajar membaca teks narrative pada siswa kelas IX semester genap tahun pelajaran 2019/2020 SMPN 3 Trenggalek mengalami peningkatan dengan nilai rata-rata siswa sebesar 84,53 dengan presentase ketuntasan sebesar 100%. Berdasarkan hasil diperoleh rata-rata nilai siswa sebesar 84,53 dengan jumlah siswa yang tuntas melakukan indikator sebanyak 32 siswa (100% dari total jumlah siswa).